Approaches to strengthen Swiss private wealth mobilisation into impact-oriented investment strategies - Gothuey, Antoine Désiré (2024)
This Master’s thesis explores a paradox at the intersection of global finance, environmental degradation, and socio-economic inequality, focusing on the challenges faced by the Swiss Wealth Management industry in directing capital towards impact-oriented investments. As human development strains natural resources and wealth inequality grows, a new generation of high-networth individuals (HNWIs) is emerging with increased awareness of these issues. Yet, their wealth remains underutilised in investments aimed at addressing these challenges. The research is based on qualitative data from interviews with professionals in the Swiss Wealth Management sector, examining how industry practices and client preferences shape the flow of private capital into sustainable investment vehicles. Findings reveal barriers such as information asymmetries, concerns over risk-adjusted returns, reputational risks, and liquidity constraints, which contribute to a cautious approach among wealth managers and their clients. The study also notes generational differences, with younger HNWIs favouring active, local impact strategies. Regulatory inconsistencies further complicate investment, particularly in emerging markets where capital is most needed. This study contributes to discussions on sustainable finance by analysing the Swiss Wealth Management industry’s role in advancing or hindering progress towards the Sustainable Development Goals (SDGs). It suggests pathways for overcoming barriers and better aligning private wealth with global sustainability goals.